Sports Medicine for Youth Soccer - Carroll, W. L.
Überblicksartikel zu den verschiedenen sportmedizinischen Aspekten des Jugendfußballs: Physiological and Chronological Age Characteristics of a Soccer Player Practice Sessions Preparations for the Soccer Season Water and Electrolyte Balance Adaptation of Endurance Training Cardiovascular - Respiratory Adaptation Common Injuries Encountered in the Sport of Soccer Youth and age group soccer can be an extremely positive experiences for the young athlete. Skill development, coordination, socialization skills, and cooperation are all positive results of a healthy youth and age group soccer program. In order to assure a healthy program, one must insist that sports medicine considerations such as preparticipation physical exams, proper conditioning, conservative injury care and warm- up and cool down periods are observed as well as adequate hydration and rehydration.